Fluorinated CYTOP passivation effects on the electrical reliability of multilayer MoS2 field-effect transistors. (16th October 2015) - Roh, Jeongkyun; Cho, In-Tak; Shin, Hyeonwoo; Woo Baek, Geun; Hee Hong, Byung; Lee, Jong-Ho; Hun Jin, Sung; Lee, Changhee
Abstract: We demonstrated highly stable multilayer molybdenum disulfide (MoS2 ) field-effect transistors (FETs) with negligible hysteresis gap (Δ V HYS ∼ 0.15 V) via a multiple annealing scheme, followed by systematic investigation for long-term air stability with time (∼50 days) of MoS2 FETs with (or without) CYTOP encapsulation. The extracted lifetime of the device with CYTOP passivation in air was dramatically improved from 7 to 377 days, and even for the short-term bias stability, the experimental threshold voltage shift, outstandingly well-matched with the stretched exponential function, indicates that the device without passivation has approximately 25% larger the barrier distribution (Δ E B = k B T o ) than that of a device with passivation. This work suggests that CYTOP encapsulation can be an efficient method to isolate external gas (O2 and H2 O) effects on the electrical performance of FETs, especially with low-dimensional active materials like MoS2 .